The geochemistry of minor elements in Pernambuco soils. IV. Zinc in the "Zona Litoral-Mata" - Horowttz, Arão; Dantas, Humberto da Silveira (Pesquisa Agropecuaria Brasileira, 2014)
Eleven soils profiles of the region known as the "Zona Litoral-Mata" in the State of Pernambuco (Brazil) were studied. These profiles are typical of the region (Coastal region). In these soils the total and extractable zinc, obtained by six different methods, were analyzed by atomic absorption spectrophotometry. The soils studied, which are the most important in the state in relation to agriculture, are normal as far as total zinc is concerned. Total zinc content ranges from 19 to 189 ppm in the surface horizon (with an average of 53 ppm). The metal tends to be more abundant in the lower horizons, where it is bounded mainly to clay minerals. The zinc is partly leached from the surface horizons, but some is retained by the soil organic matter. Through-out the profile of these soils the total zinc level is mainly controlled by the clay content. A minimal part of the zinc is retained in a form which is not easily soluble, probably entering the surface lattice of the clay minerals. It has been possible to place the soils studied in three groups according to their zinc availability. The first includes soils where zinc deficiencies are to be expected. The second group comprises the soils in which the available zinc content is near the critical level and are potentially deficient under intense cultivation. The third group includes the soil with a zinc content considered to be adequate. In all soils studied the zinc content is well below the toxicity level, and therefore symptoms of zinc excess are not likely to occour in this region. From the data obtained it is evident that most of the soils in the region studied are zinc deficient. The authors suggest that complementary research on animals and men living in these zinc deficient areas are advisable because of the effects on health in man and animals now recognized as being caused by a diet deficient in zinc.
Keywords: Geochemistry; soils; analytical chemistry; trace elements; zinc; Zona Litoral-Mata; Pernambuco; Brazil